Geriatric Conditions in Patients Undergoing Defibrillator Implantation for Prevention of Sudden Cardiac Death: Prevalence and Impact on Mortality. (January 2016) - Green, Ariel R.; Leff, Bruce; Wang, Yongfei; Spatz, Erica S.; Masoudi, Frederick A.; Peterson, Pamela N.; Daugherty, Stacie L.; Matlock, Daniel D.
Abstract : Background—: Geriatric conditions may influence outcomes among patients receiving implantable cardioverter-defibrillators (ICDs). We sought to determine the prevalence of frailty and dementia among older adults receiving primary prevention ICDs and to determine the impact of multimorbidity on mortality within 1 year of ICD implantation. Methods and Results—: The cohort included 83 792 Medicare patients from the National Cardiovascular Data Registry ICD Registry who underwent first primary prevention ICD implantation between 2006 and 2009. These data were merged with Medicare analytic files to determine the prevalence of frailty, dementia, and other conditions before ICD implantation, as well as 1-year mortality. A validated claim-based algorithm was used to identify frail patients. Mutually exclusive patterns of chronic conditions were examined. The association of each pattern with 1-year mortality was assessed using logistic regression models adjusted for selected patient characteristics. Approximately 1 in 10 Medicare patients with heart failure receiving a primary prevention ICD had frailty (10%) or dementia (1%). One-year mortality was 22% for patients with frailty, 27% for patients with dementia, and 12% in the overall cohort. Several multimorbidity patterns were associated with high 1-year mortality rates: dementia with frailty (29%), frailty with chronic obstructive pulmonary disease (25%), and frailty with diabetes mellitus (23%). These patterns were present in 8% of the cohort. Conclusions—: More than 10% of Medicare beneficiaries with heart failure receiving primary prevention ICDs have frailty or dementia. These patients had significantly higher 1-year mortality than those with other common chronic conditions. Frailty and dementia should be considered in clinical decision-making and guideline development. Abstract : Supplemental Digital Content is available in the text.